Measures of the welfare cost of inflation: a complete ordering - Turchick, David (2007)
This paper presents three contributions to the literature on the welfare cost of ináation. First, it introduces a new sensible way of measuring this cost - that of a compensating variation in consumption or income, instead of the equivalent variation notion that has been extensively used in empirical and theoretical research during the past fiftt years. We find this new measure to be interestingly related to the proxy measure of the shopping-time welfare cost of ináation introduced by Simonsen and Cysne (2001). Secondly, it discusses for which money-demand functions this and the shopping-time measure can be evaluated in an economically meaningful way. And, last but not least, it completely orders a comprehensive set of measures of the welfare cost of ináation for these money-demand specification. All of our results are extended to an economy in which there are many types of monies present, and are illustrated with the log-log money-demand specification.